Manajemen Event Rokest Party 2024 Sebagai Media Komunikasi Pengenalan Seni Grafiti - Alfareji Febrian Hanom; Bintang Awal Ramadhan; Muhamad Firzan Akbar; Qurotul Putri Riyadi; Carolina Fernanda Diaz Aprianto; Linka Azzahra; Nabilah Akhsaniyah; Gilang Wasis Danuarta; Sadiyah El Adawiyah (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
Graffiti art is a form of art that possesses unique qualities and distinct market value compared to other art forms. However, it is still often seen as vandalism that damages public property in the eyes of society. There is a need for communication channels to introduce graffiti to the Indonesian public in order to change this perception. Through the Rokest Party 2024 event held on July 6th at Cafe Kaldi.Id Juanda Depok, the Rokest community, together with Communication Science students from the Faculty of Social and Political Sciences at Muhammadiyah University of Jakarta, organized this event with the intention of introducing graffiti and promoting the market value of graffiti artworks within the Rokest community. The event implementation method followed Glodblatt's event planning model, which includes research, design, planning, coordination, and evaluation. Therefore, this event can be considered successful as a communication medium for introducing graffiti, despite needing further improvements and evaluation.